UPAYA MENINGKATKAN AKHLAK TERPUJI MELALUI METODE KISAH QUR‘ANI DAN NABAWI PADA TK. AL-DJUFRI III DESA BLUMBUNGAN KECAMATAN LARANGAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Sumiati Sumiati; M. Ridlwan; Ratno Abidin (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine the improvement of commendable morals through the method of the story of the Qur'ani and the Prophet at Kindergarten. Al-Djufri III, Blumbungan Village, Larangan District, Pamekasan Regency, 2021/2022 Academic Year. The need for improvement, individual creativity is very much felt in its growth and development in realizing development humans who can build themselves and are responsible for the development of their nation and country. The research method used in this study uses quantitative methods. The type of research used by the author in this study is a type of correlation / relationship research with the aim of determining how much variations in one factor are related to variations in one or several other factors based on the correlation coefficient. The results of the research that has been carried out turned out to be a significant positive relationship between parental motivation and the learning creativity of kindergarten students. Al-Djufri III Blumbungan Village, Larangan District, Pamekasan Regency, 2021/2022 Academic Year.Â Keywords: quantitative; motivational; variation; Qur'anic and prophetic